A taxonomy of messages about healthy behaviors recalled by adults in Chile - Peña-y-Lillo, Macarena (Revista Española de Comunicación en Salud, 2023)
Introduction: Studies of the link between exposure to health information and the adoption and maintenance of preventive behaviors often overlook the fact that within the concept of “information” there may be different categories. Objective: To explore the messages people are exposed to regarding three healthy habits: the practice of physical activity, the consumption of fruits and vegetables, and the cessation of tobacco consumption. Methods: 36 semi-structured interviews were conducted with people over 25 years of age living in the city of Santiago de Chile. Results: The messages to which people remember being exposed to can be organized into four categories: risks or negative aspects, benefits, practical information, and prescriptions. People connect some categories clearly with the adoption of behaviors, while others seem irrelevant or even detrimental. In addition, age differences are found in the recall of different categories. Conclusion: This study underlines the need to break down the concept of health information when one wants to study its impact on people’s health decisions, taking into account that the subjects’ informative environments comprise different types of messages and that they do not all push in the desired direction.